Tempeh Soybean And Banana Cookies Increasing Weight To Wasting Toddler - Rotua, Manuntun; Sihite, Nathasa Weisdania (Chakra Brahmanda Lentera Institute, 2023)
Background: Wasting is caused by insufficient nutritional intake or disease in children. This situation results in reduced weight in children so that the child's weight is disproportionate to his height. The impact of wasting on children is a decrease in export power to their environment, increased frequency of crying, less sociability with fellow children, fewer feelings of joy, and a tendency to become apathetic. To overcome the problem of wasting, Indonesia has done various ways, including supplementary feeding. The research aimed to know the effect of giving soybean tempeh cookies and kepok bananas at the Sukarami Health Center in Palembang City on increasing the weight of wasting toddlers. Methods: This type of research is quasi-experimental, using a one-group pretest-postest research design. Research sampling using the Lameshow formula as many as 60 samples. Data analysis using t-dependent test and t-independent test Results: The results showed that the average body weight of the treatment group respondents before the intervention was 9.38 kg, and after the intervention, it was 9.65 kg. The average body weight of the control group before the intervention was 9.95 kg, and after the intervention, it was 10.01 kg. The difference in the average change in body weight of respondents before and after treatment in the treatment group was 0.27kg, and in the control, 0.06 kg. There is an effect of giving soybean tempeh cookies and kepok bananas on increasing the weight of wasting toddlers with a p-value of 0.014. Conclusion: Providing Supplementary Food can be added seller because children like sales from organic ingredients (fruits and vegetables) for a longer time, so the effect can be more visible in increasing the weight of toddler wasting